Healthcare-Associated Infections-Related Bacteriome and Antimicrobial Resistance Profiling: Assessing Contamination Hotspots in a Developing Country Public Hospital - Sereia, Aline Fernanda Rodrigues; Christoff, Ana Paula; Cruz, Giuliano Netto Flores; da Cunha, Patrícia Amorim; da Cruz, Guilherme Cezar Kniphoff; Tartari, Daniela Cristina; Zamparette, Caetana Paes; Klein, Taise Costa Ribeiro; Masukawa, Ivete Ioshiko; Silva, Clarice Iomara; e Vieira, Maria Luiza Vieira; Scheffer, Mara Cristina; et al. (Frontiers in Microbiology, 2021)
Hospital-built environment colonization by healthcare-associated infections-related bacteria (HAIrB) and the interaction with their occupants have been studied to support more effective tools for HAI control. To investigate HAIrB dynamics and antimicrobial resistance (AMR) profile we carried out a six-month surveillance program in a developing country public hospital, targeting patients, hospital environment, and healthcare workers, using culture-dependent and culture-independent 16S rRNA gene sequencing methods. The bacterial abundance in both approaches shows that the HAIrB group has important representativeness, with the taxa Enterobacteriaceae, Pseudomonas, Staphylococcus, E. coli, and A. baumannii widely dispersed and abundant over the time at the five different hospital units included in the survey. We observed a high abundance of HAIrB in the patient rectum, hands, and nasal sites. In the healthcare workers, the HAIrB distribution was similar for the hands, protective clothing, and mobile phones. In the hospital environment, the healthcare workers resting areas, bathrooms, and bed equipment presented a wide distribution of HAIrB and AMR, being classified as contamination hotspots. AMR is highest in patients, followed by the environment and healthcare workers. The most frequently detected genes were, blaSHV-like, blaOXA-23-like, blaOXA-51-like, blaKPC-like, blaCTX-M-1, blaCTX-M-8, and blaCTX-M-9 groups. Our results demonstrate that there is a wide spread of antimicrobial resistance due to HAIrB in the hospital environment, circulating among patients and healthcare workers. The contamination hotspots identified proved to be constant over time. In the fight for patient safety, these findings can reorient practices and help to set up new guidelines for HAI control.